Produção de forragem e atributos químicos e físicos do solo em sistemas integrados de produção agropecuária - Bonini, Carolina dos Santos Batista [UNESP]; Lupatini, Gelci Carlos [UNESP]; Andrighetto, Cristiana [UNESP]; Mateus, Gustavo Pavan; Heinrichs, Reges [UNESP]; Aranha, Aline Sampaio [UNESP]; de Santana, Erikelly Aline Ribeiro [UNESP]; Meirelles, Guilherme Constantino [UNESP] (FapUNIFESP (SciELO), 2016)
The objective of this work was to evaluate the forage production of 'Marandu' palisade grass (Urochloa brizantha) and the soil chemical and physical attributes in integrated agricultural systems. Croplivestock and crop-livestock-forest integrated systems were evaluated in single (200 trees per hectare) and triple planting lines (500 trees per hectare), besides the exclusive planting of eucalyptus. Soil mechanical resistance to penetration and forage production did not differ between systems. Soil-water infiltration was lower in the agroforestry systems. After two years of the implementation of the systems, the levels of organic matter, calcium, magnesium, and phosphorus increased in the 0-20-cm soil depth.
Forage production and soil chemical and physical attributes in integrated agricultural systems
Keywords: 'Marandu' palisade grass; Agrosylvopastoral systems; Infiltration rate; Organic matter; Urochloa brizantha